Mindfulness-Based Stress Reduction on breast cancer symptoms: systematic review and meta-analysis - Castanhel, Flavia Del (Einstein (Sao Paulo), 2018)
Mindfulness-Based Stress Reduction practices increase the capacity for concentration and attention, and these practices are particularly effective for people with breast cancer. To analyze the effects of the application of Mindfulness-Based Stress Reduction on breast cancer symptoms. Systematic review and meta-analysis were carried out. To find suitable studies, the PubMed/ MEDLINE database was searched using the keywords “breast cancer” and “Mindfulness-Based Stress Reduction”. Studies included were published between 2013 and 2017, written in English and showed methodological quality through the PEDro scale (score greater than 3). They also presented empirical evidence, had an experimental study design (randomized or non-randomized), and had full text available. For the meta-analysis, we used a random-effects model, with standardized mean differences and 95% confidence intervals. Seven studies were included, one non-randomized and containing only an intervention group of Mindfulness-Based Stress Reduction, and six randomized including samples of two or three groups. The non-randomized study showed 6 points on the PEDro scale, the randomized studies of two groups 6 to 7 points and studies with three groups showed 7 points. In the meta-analysis of the two randomized studies, the results, although not significant, revealed a moderate effect for Mindfulness-Based Stress Reduction on the outcome of fatigue, with a mean difference of −0.42 (95%CI −0.92- −0.07; p=0.09). Mindfulness-Based Stress Reduction seems to be a promising alternative for treatment of this disease's symptoms.